If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -3 = 7 Reorder the terms: -3 + -6x = 7 Solving -3 + -6x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -6x = 7 + 3 Combine like terms: -3 + 3 = 0 0 + -6x = 7 + 3 -6x = 7 + 3 Combine like terms: 7 + 3 = 10 -6x = 10 Divide each side by '-6'. x = -1.666666667 Simplifying x = -1.666666667
| 8x-6-2x=4 | | 44x+9=7(6x+2)+2x-5 | | 10(2t+5)-8t=56 | | 4(5b-1)-(3b-7)=7-(5b+4) | | 5t=4t-8 | | 7/10=x/7 | | 2(5c+1)-(4c-5)=5-(5c-2) | | cos(4x)=cos(6x) | | 8-(4x+6)=0.5(5-7x) | | (5u+4)(7+u)=0 | | 14x(-3x+5)=3 | | x*2+y=36 | | 14x(3x-5)=82 | | 9w^6+24w^5+16w^4=0 | | 3(3z+4)-4(2z-3)=8 | | 4y^4+18y^3-10y^2=0 | | 7z^2-20z-3=0 | | (3x)2-10= | | -18-12/-18+12= | | 8z-4(z-5)+4=4z-16 | | -15-(-4)-7= | | 8z-4(z-5)+4= | | (61000-x)/21350 | | 4x-3(3x-1)+12=15(x+9) | | -4(3-10)= | | -5+(-16)+9= | | 7n^2+14n+5=0 | | r=exp(0.09)-1 | | 20-11=3(x-3) | | 50+5y-17=17y-12-3y | | 36/-4= | | y=1x+16 |